Analisis Pengaruh Faktor Inflasi dan Indeks Harga Konsumen Terhadap Nilai Tukar Petani Subsektor Peternakan di Provinsi Jambi Periode Tahun 2014-2022 - Firmansyah, Firmansyah; Hoesni, Fachroerrozi; Farizal, Farizal; Ananda, Fira Dwi (Ekonomis: Journal of Economics and Business, 2024)
The purpose of this research is to see the development of the Farmer Exchange Rate (NTP) of the Livestock Subsector and to determine the effect of the Consumer Price Index (CPI) and inflation on the NTP of the Jambi Province livestock subsector during the 2014-2022 time span. The data used in this study are secondary data from the Central Statistics Agency (BPS). Data analysis uses a computer with the help of Eviews software to test the factors that affect the NTP of the livestock subsector using the multiple linear regression method. The results of the analysis show that the CPI has a significant effect on the NTP of the livestock subsector while inflation does not affect it. It can be concluded that the NTP of livestock subsector in Jambi Province tends to decrease and is significantly influenced by CPI but not by inflation.